Plasmon-enhanced homogeneous and heterogeneous triplet–triplet annihilation by gold nanoparticles1. Issue 22 (14th June 2015) - Cao, Xian; Hu, Bo; Ding, Rui; Zhang, Peng
<x xml:space="preserve">Abstract</x> We report the investigation of surface plasmon induced enhancement of homogeneous and heterogeneous triplet–triplet annihilation by gold nanoparticles.